2016
DOI: 10.1038/srep30792
|View full text |Cite|
|
Sign up to set email alerts
|

Angelman syndrome-derived neurons display late onset of paternal UBE3A silencing

Abstract: Genomic imprinting is an epigenetic phenomenon resulting in parent-of-origin-specific gene expression that is regulated by a differentially methylated region. Gene mutations or failures in the imprinting process lead to the development of imprinting disorders, such as Angelman syndrome. The symptoms of Angelman syndrome are caused by the absence of functional UBE3A protein in neurons of the brain. To create a human neuronal model for Angelman syndrome, we reprogrammed dermal fibroblasts of a patient carrying a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 29 publications
9
43
1
1
Order By: Relevance
“…Vector particle production (see Supplemental Experimental Procedures) was performed as previously described (Stanurova et al., 2016). Primary fibroblasts were cultured up to 80% confluence.…”
Section: Methodsmentioning
confidence: 99%
“…Vector particle production (see Supplemental Experimental Procedures) was performed as previously described (Stanurova et al., 2016). Primary fibroblasts were cultured up to 80% confluence.…”
Section: Methodsmentioning
confidence: 99%
“…The silencing of paternal UBE3A is also associated with a long, non-coding antisense RNA (UBE3A-ATS). As cells differentiate into neurons, UBE3A-ATS expression increases to a high enough level to silence paternal UBE3A, potentially through a hypothesized collision mechanism (Hsiao et al, 2019;Stanurova et al, 2016) between these two opposed and overlapping transcripts.…”
Section: Hcos Reveal Distinct Patterns Of Ube3a Expression In Progenimentioning
confidence: 99%
“…However, at 4 weeks, we observed only a reduction in UBE3A-ATS and did not detect an increase in UBE3A expression ( Figure 4D). This could be attributed to a delay between transcription of UBE3A-ATS and silencing of UBE3A (Hsiao et al, 2019;Stanurova et al, 2016) (Figures 3A and 3B) so that UBE3A expression levels are still high at that stage of hCO development.…”
Section: Hcos Reveal Distinct Patterns Of Ube3a Expression In Progenimentioning
confidence: 99%
“…However, hypermethylation has not been obvious in iPSC studies . Changes in the UBE3A gene affect the functional maturation of neurons, and the appearance of AMPA receptor–mediated excitatory postsynaptic currents (EPSCs) in patient‐derived neurons is significantly delayed . In the late stage of neuronal development and maturation, the resting membrane potential exhibits depolarization, decreased spontaneous excitatory postsynaptic action potentials, decreased neuron activity, and decreased synaptic plasticity.…”
Section: Ipsc Studies On the Molecular Mechanisms Of Gementioning
confidence: 99%
“…86,87 Changes in the UBE3A gene affect the functional maturation of neurons, and the appearance of AMPA receptor-mediated excitatory postsynaptic currents (EPSCs) in patient-derived neurons is significantly delayed. 88 In the late stage of neuronal development and maturation, the resting membrane potential exhibits depolarization, decreased spontaneous excitatory postsynaptic action potentials, decreased neuron activity, and decreased synaptic plasticity. In combination with the CRISPR/Cas9 gene-editing technique, it was demonstrated that the depolarization of the resting membrane potential induced by the UBE3A mutation might be an important cause of altered cell activity.…”
Section: Mutations Affecting Neurite Maturationmentioning
confidence: 99%